1994
DOI: 10.1161/01.res.74.3.507
|View full text |Cite
|
Sign up to set email alerts
|

Significance of inwardly directed transmembrane current in determination of local myocardial electrical activation during ventricular fibrillation.

Abstract: Ventricular fibrillation (VF) is the principle cardiac rhythm disorder responsible for sudden cardiac death in humans. The accurate determination of local cardiac activation during VF is essential for its mechanistic elucidation. This has been hampered by the rapidly changing and markedly heterogeneous electrophysiological nature of VF. These difficulties are manifested when attempting to differentiate true propagating electrical activity from electrotonic signals and when identifying local activation from com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…On the other hand, the "fiber-optic pickup" probe comprises a single optical fiber to deliver excitation light from the laser to the myocardium and six surrounding optical fibers to return the dye fluorescence from the myocardium to the photodetector [73,74]. The pickup probe is placed close to the myocardium stained with a voltage-sensitive fluorescent dye.…”
Section: Optical Recording System Using Fiber Opticsmentioning
confidence: 99%
“…On the other hand, the "fiber-optic pickup" probe comprises a single optical fiber to deliver excitation light from the laser to the myocardium and six surrounding optical fibers to return the dye fluorescence from the myocardium to the photodetector [73,74]. The pickup probe is placed close to the myocardium stained with a voltage-sensitive fluorescent dye.…”
Section: Optical Recording System Using Fiber Opticsmentioning
confidence: 99%
“…Witkowski and Kavanagh and their colleagues developed the Transmembrane Current Method (TCM) for differentiating between local activations and distant activity. TCM is used to estimate a value proportional to the transmembrane current (8). Blanchard and her co-workers showed that the Rule-Based Method (RBM) in combination with TCM can be useful for determining the locations of electrical activations during VF (9).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to measure potentials at this resolution can aid in measuring or eliminating the potential gradient between the interstitium and the extracellular volume conductive medium. This may further improve the SL measurement technique, defined as the second spatial derivative of the field potential on the heart surface, which was reported to be superior to the unipolar electrogram (potential difference between the exploring electrode to the reference electrode) for the detection of local activation during ventricular fibrillation [19,20]. The in-vivo transmembrance current density (1m) calculated using the Surface Laplacian technique may be improved as suggested in previous simulation studies [21].…”
Section: Purposementioning
confidence: 95%
“…It has been reported that the Surface Laplacian electrogram is superior to the unipolar electrogram in detecting local activation time during VF [20,22,23]. Also, SL morphologies can determine the activation block and wavefront initiation, and improve the transmembrance current density calculation [23].…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation